1992
DOI: 10.1577/1548-8667(1992)004<0114:doasit>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofAeromonas salmonicidain the Mucus of Salmonid Fishes

Abstract: Mucus of salmonids was evaluated as a source for nonlethal detection of the pathogen Aeromonas salmonicida in fish. The bacterium was readily isolated from mucus on dilution plates when Coomassie Brilliant Blue agar was the primary plating medium. Kidney samples from the fish that served as sources of mucus were similarly processed. Infection was detected in 56% of mucus samples from lake trout Salvelinus namaycush that were undergoing an epizootic of furunculosis, but only 6% of the kidneys from these fish we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 0 publications
5
29
0
1
Order By: Relevance
“…The AP and PAAS PCRs were also used to detect Aeromonas salmonicida in tissue and mucus samples taken from the overtly diseased fish. Cipriano et al (1992Cipriano et al ( , 1994bCipriano et al ( , 1996a) have previously reported levels of A. salmonicida in overtly infected fish, including Atlantic salmon, ranging from 10 3 to 10 7 CFU g -1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AP and PAAS PCRs were also used to detect Aeromonas salmonicida in tissue and mucus samples taken from the overtly diseased fish. Cipriano et al (1992Cipriano et al ( , 1994bCipriano et al ( , 1996a) have previously reported levels of A. salmonicida in overtly infected fish, including Atlantic salmon, ranging from 10 3 to 10 7 CFU g -1…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria were isolated from the infected fish tissues (gill, spleen, kidney and intestine) and mucus, and were identified according to the method of Cipriano et al (1992).…”
Section: Overt Infection Inmentioning
confidence: 99%
“…Klontz (1968) suggested that the primary site of carnage was the intestine and reported the detection of asymptomatic infections by fluorescent antibody examination of intestinal swabs. Cipriano et al (1992) deduced the asymptomatic infection status of fish populations from their previous clinical histories and suggested that bacterial culture of the mucus was of value.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, all samples from fish and sediment from the pond were routinely plated on selective media designed for the recovery of Y. ruckeri (ribose-ornithindextrin agar [ROD] [13]), A. salmonicida (Coomassie brilliant blue [10]), and Aeromonas hydrophila (Pril-ampicillin-dextrin-ethanol [PADE] agar [21]). Coomassie brilliant blue and PADE agar plates were incubated at 20°C for 2 days, and ROD agar plates were incubated at 20°C for 4 days.…”
mentioning
confidence: 99%